"The moment you realise someone wants your body:" neoliberalism, mindfulness and female embodiment in Fleabag. Issue 1 (2nd January 2022) - Darling, Orlaith
ABSTRACT: Phoebe Waller Bridge's Fleabag aired on the BBC in 2016 and 2019 to huge critical acclaim and popular interest. Following the fragmented and chaotic life of Fleabag, a London-based young woman, the series charts the anxieties pervading contemporary society, particularly those pertaining to female sexuality, embodimentand subjectivity. This article focuses on the difficulties of female embodiment under neoliberalism, arguing that the "excess" traditionally attributed to female embodiment is weaponised by neoliberal privileging of individualism, self-managementmanagement, and self-control. Tropes of female "excess" are peppered throughout the series, from the resurgence of a naked female torso statue, to the dead and the "failing" maternal body, to the yoga and mindfulness particularly marketed at women. Fleabag is juxtaposed with her sister Claire, who is presented as an ideal neoliberal subject due to her disavowal of female embodiment; by contrast, Fleabag's "excess" means that her body becomes a site onto which anxiety arising from neoliberal society is projected. Ultimately, however, this article finds that Fleabag's openness and repudiation of neoliberal values allows her to become a connective body, bringing other women into more authentic embodiment, foregrounding the gendered violence of neoliberalism and retaining focus on absent and effaced female bodies such as her mother and Boo.